UPAYA MENINGKATKAN MINAT BELAJAR MATEMATIKA DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) - ., Sarinem; Hidayati, Ika Septi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Cokroaminoto Yogyakarta, 2022)
The purpose of this study was 1) to find out the application of the Team Assisted Individualization (TAI) Cooperative learning model in order to increase the learning interest of the fifth grade students of Tangkisan State Elementary School.. The results of this study indicate that: (1) In general, the application of the appropriate TAI learning model is effective in improving mathematics learning achievement, (2) Increased mathematics learning achievement of fifth grade elementary school students at Tangkisan at 61.07 in the first cycle of 75, 31 in the second cycle of 84.69